Ankle control differentiation as a mechanism for mobility limitations. (27th July 2020) - James, Eric G.; Hausdorff, Jeffrey M.; Leveille, Suzanne G.; Travison, Thomas; Bean, Jonathan F.
Highlights: Low foot differentiation is associated with high coordination variability. Low foot differentiation is associated with mobility limitations. Low foot differentiation may be a mechanism of mobility limitations. Abstract: Independent control of the right and left ankles (differentiation) may be a motor control mechanism linking impaired coordination and mobility limitations. We tested the hypotheses that motor control differentiation of the ankles, as measured using Cross-Sample Entropy, during antiphase coordination at two movement frequencies, is associated with impaired coordination (high ankle coordination variability) and mobility limitations (Short Physical Performance Battery score ≤9). We conducted a cross-sectional study of community-dwelling older adults (N = 133) aged 80.04 (±4.67) years. In linear regression modeling, low ankle Cross-Sample Entropy (low motor control differentiation) was associated with poor (i.e., high) coordination variability at the slower (P = 0.026), but not the faster (P = 0.447), ankle movement frequency. In logistic regression modeling, low Cross-Sample Entropy at the slower (OR = 1.67; 95 % CI: 1.07–2.59) and faster (OR = 2.38; 95 % CI: 1.43–3.94) ankle movement frequencies were associated with increased odds for mobility limitations. Our findings support the hypothesis that ankle differentiation may be a motor control mechanism that links impaired coordination with mobility limitations.